2023
DOI: 10.1007/s10040-023-02635-4
|View full text |Cite
|
Sign up to set email alerts
|

How to conduct variable-density sand tank experiments: practical hints and tips

Abstract: Sand tank experiments are a powerful tool for the investigation and visualization of groundwater flow dynamics. Especially when studying coastal aquifers, where the presence of both fresh and saline water induces complex variable-density flow and transport processes, the controlled laboratory settings of tank experiments help scientists to identify general patterns and features. This technical note provides practical information on planning, conducting and evaluating sand tank experiments, with a focus on appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…To fully understand the effect of the iron-curtain on solute exchange at the land sea transition zone, comprehensive investigations on redox-processes-and associated secondary reactions are required. As field sites are often difficult to access, the replica of a beach aquifer under laboratory conditions can aid to better understand the fundamentals of the involved physical and biogeochemical processes (Stoeckl & Houben, 2023). For instance, Röper et al (2014), Shen et al (2015), Zhang et al (2017) or Delwar et al (2024) mimicked coastal aquifers in laboratory experiments and found the freshwater-seawater interface in the STE to be far less stable than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…To fully understand the effect of the iron-curtain on solute exchange at the land sea transition zone, comprehensive investigations on redox-processes-and associated secondary reactions are required. As field sites are often difficult to access, the replica of a beach aquifer under laboratory conditions can aid to better understand the fundamentals of the involved physical and biogeochemical processes (Stoeckl & Houben, 2023). For instance, Röper et al (2014), Shen et al (2015), Zhang et al (2017) or Delwar et al (2024) mimicked coastal aquifers in laboratory experiments and found the freshwater-seawater interface in the STE to be far less stable than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…Physical model tests have become one of the effective methods for studying seawater intrusion. Sand tank experiments are a powerful tool for the investigation and visualization of seawater intrusion, which can help researchers to identify general patterns and features [38]. Numerous experimental studies on seawater intrusion have been conducted by scholars [39][40][41].…”
Section: Introductionmentioning
confidence: 99%